2021
DOI: 10.3390/plants10030525
|View full text |Cite
|
Sign up to set email alerts
|

Cottonseed Protein, Oil, and Minerals in Cotton (Gossypium hirsutum L.) Lines Differing in Curly Leaf Morphology

Abstract: Cottonseed is an important source of protein, oil, and minerals for human health and livestock feed. Therefore, understanding the physiological and genetic traits influencing the nutrient content is critical. To our knowledge, there is no information available on the effects of leaf shape—curly leaf (CRL)—on cottonseed protein, oil, and minerals. Therefore, the objective of the current research was to investigate the effect of the curly leaf trait on cottonseed protein, oil, and minerals in cotton lines differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Selected chemical components of Gd and Gl cottonseed kernels are listed in Table 1 . These data are generally in the range described in the literature [ 56 , 57 , 58 , 59 ]. The unique features in the presence or absence of gossypol are clearly demonstrated by the difference in gossypol content between the two types of cottonseeds.…”
Section: Resultsmentioning
confidence: 83%
“…Selected chemical components of Gd and Gl cottonseed kernels are listed in Table 1 . These data are generally in the range described in the literature [ 56 , 57 , 58 , 59 ]. The unique features in the presence or absence of gossypol are clearly demonstrated by the difference in gossypol content between the two types of cottonseeds.…”
Section: Resultsmentioning
confidence: 83%
“…The negative response of nutrients in some CS lines was shown in, for example, CS-B02, CS-B04, and CS-M04 for C. It must be noted here that some seed nutrients showed different location responses in some CS lines, reflecting the significant effects of environmental conditions at each location. Previous research on other seed traits also showed different responses, depending on the environmental factors of each location, including soil type, temperature, drought, and other environmental conditions [13]. For example, during the critical months of growth (May through September), the temperature was higher in Mississippi state (Starkville, MS) than in Florence, SC, and precipitation was higher in Mississippi state (Starkville), except in July.…”
Section: Discussionmentioning
confidence: 97%
“…Nutrient accumulation in seeds is controlled by several processes, including nutrient uptake, translocation, redistribution, and accumulation [11,12]. Inheritance and genetic mechanisms of these processes need further research if ways to control these processes are to be identified [1,13]. The principal physiological and metabolic functions of plant macronutrients, including Ca, K, Mg, N, P, and S, are well documented [14,15], and quantitative trait loci (QTL) associated with mineral accumulation in seeds were identified for rice [16], wheat [17], and the alfalfa-related model organism Medicago truncatula [18]; limited QTLs were identified for the macronutrients Ca, Mg, K, N, S, and P in soybean seed [19].…”
Section: Introductionmentioning
confidence: 99%
“…These components are uniquely distributed across different layers within the plant species (Fang, 2018;Salem et al, 2022). Beyond its pivotal role in the textile industry, cotton fiber's seeds emerge as a valuable source of protein, oil, and minerals, heralding potential benefits for human health and livestock nutrition (Bellaloui et al, 2021). While cotton once stood as a cornerstone of Ecuador's agricultural sector, its cultivation area has seen a gradual decline over the years (García et al, 2019).…”
Section: Introductionmentioning
confidence: 99%